The meat paradox and health-related aspects: A cluster analysis among red meat consumers - Riccardo Testa; Giuseppina Rizzo; Riccardo Vecchio; Francesco Vella; Giorgio Schifani; Giuseppina Migliore (Food Quality and Preference, 2025)

Turbulent erosion of a subducting intrusion in the Western Mediterranean Sea - Giovanni Testa; Mathieu Dever; Mara Freilich; Amala Mahadevan; T. M. Shaun Johnston; Lorenzo Pasculli; Francesco M. Falcieri (Ocean Science, 2025)
Frontal zones within the Western Alboran Gyre (WAG) are characterized by a density gradient resulting from the convergence of Atlantic and Mediterranean waters. Subduction along isopycnals at the WAG periphery can play a crucial role in upper-ocean ventilation and influences its stratification and biogeochemical cycles. In 2019, physical parameters (comprising temperature, salinity, turbulent kinetic energy dissipation rates) and biogeochemical data (oxygen and chlorophyll a) profiles were collected in transects along the northern edge of the WAG. Several intrusions of subducted water with elevated oxygen, chlorophyll a, and spice anomaly were identified towards the center of the anticyclone. These features had elevated kinetic energy dissipation rates on both their upper and lower boundaries. Analysis of the turbulent fluxes involving heat, salt, oxygen, and chlorophyll a demonstrated a net flux of physical and biogeochemical properties from the intrusions to the surrounding ocean. Either the turbulent or diffusive convection mixing contributed to the observed dilution of the intrusion. Other factors (e.g., water column density stability, variability of the photic layer depth, and organic matter degradation) likely played a role in these dynamics. Enhanced comprehension of the persistence and extent of these features might lead to an improved quantitative parameterization of relevant physical and biogeochemical properties involved in subduction within the study zone.

What drives and obstacles the intention to purchase green skincare products? A study of the Italian market of green skincare products - Riccardo Testa; Francesco Vella; Giuseppina Rizzo; Giorgio Schifani; Giuseppina Migliore (Journal of Cleaner Production, 2024)

Probabilistic fault displacement Hazard analysis in an extensional setting: Application to a strategic Dam and methodological implications - Alessio Testa; Paolo Boncio; Bruno Pace; Francesco Mirabella; Cristina Pauselli; Maurizio Ercoli; Eugenio Auciello; Francesco Visini; Stéphane Baize (Engineering Geology, 2024)

ISO 59000 Standards for the Circular Economy: a Call for Accuracy - Iñaki Heras-Saizarbitoria; Olivier Boiral; Francesco Testa (Circular Economy and Sustainability, 2024)
With the expressed aim of reducing uncertainty and lack of precision about the Circular Economy paradigm, several standards are being proposed by standard-setting bodies. The world’s most prominent body — the International Organization for Standardization — is developing the ISO 59000 family of standards to establish a common language and conceptual framework for the Circular Economy. In the light of the vigorous debate in the scientific literature about the Circular Economy, as well as criticism of the concepts involved, this perspective article calls for more precision in the definition of this type of standard.

Addressing Plastic Concern: Behavioral Insights into Recycled Plastic Products and Packaging in a Circular Economy - Filippo Corsini; Natalia Marzia Gusmerotti; Edoardo Bartoletti; Francesco Testa; Andrea Appolloni; Fabio Iraldo (Circular Economy and Sustainability, 2024)
The excessive production and use of new plastic materials pose a critical environmental challenge, and reducing its consumption has emerged as a major global hurdle. Understanding human behavior is thus essential for creating a circular economy for plastics. The study aims to gain insights into consumers' buying habits concerning recycled plastic, which has received relatively little attention in prior research on the subject of environmentally friendly consumer behavior. This study draws on the Theory of Planned Behavior to analyze the factors influencing consumer behavior regarding products and packaging made from recycled plastic. To this end, we employed a questionnaire, which was administered to 511 consumers in Italy. Results support that concerns about plastics and perceived efficacy exert a direct influence on attitudes. Additionally, our findings demonstrate that social norms, attitudes, and perceived behavioral control significantly shape purchasing behaviors concerning recycled plastic. The research contributes to extending the Theory of Planned Behavior model in predicting environmental-friendly behavior by adding new empirical evidence and provides valuable suggestions for companies to develop effective communication strategies and policies to redirect plastic consumption behavior towards less-impacting use of plastic.

Diversity of plant pollen sources, microbial communities, and phenolic compounds present in bee pollen and bee bread - Massimo Iorizzo; Gianluca Albanese; Francesco Letizia; Bruno Testa; Dalila Di Criscio; Sonia Petrarca; Catello Di Martino; Sonia Ganassi; Pasquale Avino; Gianfranco Pannella; Zeineb Aturki; Cosimo Tedino; et al. (Environmental Science and Pollution Research, 2024)

Determinants of environmental social and governance (ESG) performance: A systematic literature review - Alice Martiny; Jonathan Taglialatela; Francesco Testa; Fabio Iraldo (Journal of Cleaner Production, 2024)

Correction: Observed damage and simplified risk assessment of Italian masonry bell towers struck by past seismic events - Francesco Testa; Alberto Barontini; Nicola Chieffo; Paulo B. Lourenço (Bulletin of Earthquake Engineering, 2024)

Observed damage and simplified risk assessment of Italian masonry bell towers struck by past seismic events - Francesco Testa; Alberto Barontini; Nicola Chieffo; Paulo B. Lourenço (Bulletin of Earthquake Engineering, 2024)

How companies navigate circular economy paradoxes: An organizational perspective - Duccio Tosi; Natalia Marzia Gusmerotti; Francesco Testa; Marco Frey (Journal of Environmental Management, 2024)

Green work climate, work meaningfulness and supervisor environmental priority: A social exchange perspective on employees' eco-initiatives - Natalia Marzia Gusmerotti; Niccolò Maria Todaro; Duccio Tosi; Francesco Testa (Journal of Cleaner Production, 2023)

Understanding the consumption of plant-based meat alternatives and the role of health-related aspects. A study of the Italian market - Giuseppina Rizzo; Riccardo Testa; Emilia Cubero Dudinskaya; Serena Mandolesi; Francesco Solfanelli; Raffaele Zanoli; Giorgio Schifani; Giuseppina Migliore (International Journal of Gastronomy and Food Science, 2023)

How to overcome barriers limiting LCA adoption? The role of a collaborative and multi-stakeholder approach - Francesco Testa; Sara Tessitore; Patrizia Buttol; Fabio Iraldo; Sara Cortesi (The International Journal of Life Cycle Assessment, 2022)

Drivers to green consumption: a systematic review - Francesco Testa; Gaia Pretner; Roberta Iovino; Guia Bianchi; Sara Tessitore; Fabio Iraldo (Environment, Development and Sustainability, 2021)

Perceptions on LCA implementation: evidence from a survey on adopters and nonadopters in Italy - Francesco Testa; Benedetta Nucci; Sara Tessitore; Fabio Iraldo; Tiberio Daddi (The International Journal of Life Cycle Assessment, 2016)

Enhancing the Adoption of Life Cycle Assessment by Small and Medium Enterprises Grouped in an Industrial Cluster: A Case Study of the Tanning Cluster in Tuscany (Italy) - Tiberio Daddi; Benedetta Nucci; Fabio Iraldo; Francesco Testa (Journal of Industrial Ecology, 2016)
Summary Greenhouse gas emissions from small and medium enterprises (SMEs) account for 70% of the industrial pollution in the European Union. Owing to limited economic and human resources, only a few SMEs start procedures to evaluate the environmental impact of processes and products through life cycle assessment (LCA). In this work, a cluster life cycle assessment (Cluster‐LCA) is proposed as an instrument for the diffusion and realization of LCA analysis in clustered SMEs. This methodology is illustrated with a case study in the tanning cluster in Tuscany. The different characteristics of the methodology are analyzed by identifying the intrinsic strengths, weaknesses, opportunities, and threats. The application of this methodology in a particular cluster is then discussed in order to gather some helpful insight for the application of this methodology in different clusters.

Examining green public procurement using content analysis: existing difficulties for procurers and useful recommendations - Francesco Testa; Paolo Grappio; Natalia M. Gusmerotti; Fabio Iraldo; Marco Frey (Environment, Development and Sustainability, 2016)

Mortality in a cohort of cement workers in a plant of Central Italy - Felice Giordano; Valerio Dell’Orco; Fiorella Fantini; Francesco Grippo; Vladimiro Perretta; Angelo Testa; Irene Figà-Talamanca (International Archives of Occupational and Environmental Health, 2012)

Constitutive over-expression of two wheat pathogenesis-related genes enhances resistance of tobacco plants to Phytophthora nicotianae - Floriana Fiocchetti; Rosalinda D’Amore; Monica De Palma; Laura Bertini; Carla Caruso; Carlo Caporale; Antonino Testa; Gennaro Cristinzio; Francesco Saccardo; Marina Tucci (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Proteasome inhibitors sensitize ovarian cancer cells to TRAIL induced apoptosis - Ernestina Saulle; Alessia Petronelli; Luca Pasquini; Eleonora Petrucci; Gualtiero Mariani; Mauro Biffoni; Gianluigi Ferretti; Giovanni Scambia; Pierluigi Benedetti-Panici; Francesco Cognetti; Robin Humphreys; Cesare Peschle; et al. (Apoptosis, 2007)

Cytomorphological study on human submandibular gland following treatment with secretagogue drugs - Francesca Testa Riva; Roberto Puxeddu; Francesco Loy; Gabriele Conti; Alessandro Riva (Cell and Tissue Research, 2006)